2005
DOI: 10.1021/mp050040f
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Peptide-Based Anthrax Toxin Inhibitors

Abstract: We have identified an optimized peptide inhibitor that can be used to develop potent anthrax toxin therapeutics. Anthrax toxin, an essential virulence factor of Bacillus anthracis, elicits many of the symptoms associated with the disease, and is responsible for death. The toxin is composed of a cell-binding component, protective antigen, and two enzymatic components, edema factor and lethal factor. The three proteins are secreted individually by the bacterium and then assemble into functional complexes on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
0
37
1
Order By: Relevance
“…This information serves as a foundation for the development of future polymer constructs that inhibit LF and EF transport through the PA 63 pore. Peptide inhibitors of PA 63 mediated translocation of EF and LF have been identified, but the interaction between these inhibitors and PA are generally too weak to be clinically relevant [71,72]. However, the multivalent display of these ligands on a linear polymeric backbone has increased their therapeutic efficacy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This information serves as a foundation for the development of future polymer constructs that inhibit LF and EF transport through the PA 63 pore. Peptide inhibitors of PA 63 mediated translocation of EF and LF have been identified, but the interaction between these inhibitors and PA are generally too weak to be clinically relevant [71,72]. However, the multivalent display of these ligands on a linear polymeric backbone has increased their therapeutic efficacy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The authors also emphasized that the use of a polymer with a flexible backbone (Fig. 3A) (74) would allow the drug designers to avoid the necessity of knowing the spatial relationships among the binding sites on the target, thus extending the applicability of the approach to targets in which these relationships are not yet understood. This approach was further advanced by designing functionalized liposomes of ~50 nm in size, which were allowed to interact with a cysteine-derivatized version of the earlier identified (73) PA 63 binding peptides (75).…”
Section: Pa Lf and Ef As Antitoxin Design Targetsmentioning
confidence: 99%
“…(A) After being cleaved by extracellular furin protease to a 63-kDa form, PA 63 oligomerizes and binds either EF/LF or a peptide-based inhibitor (74). (B) Design of polyvalent inhibitors with control over the molecular weight and ligand spacing (76).…”
Section: Article Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous work concluded that the 6-mer peptide sequence "TYWWLD" in the 12-mer peptide "HTSTYWWLDGAP" was both necessary and sufficient for ligand binding to PA 63 . [28] In addition, previous mutagenesis studies investigating the interactions between a library of PA mutants and phage presenting the sequence HYTYWWLD had found that the residues P184, L187, K197 and R200 on PA 63 (indicated by black dots in Scheme 2A and represented by a black rectangular sector symbol in Scheme 2B and 2C) were important for the binding of the peptide ligand to (PA 63 ) 7 . [14] From the crystal structure of (PA 63 ) 7 , [29] we calculated that the distances between these four amino acid residues on adjacent PA 63 monomers of (PA 63 ) 7 were in the 25-35 Å range (Table S1 and Scheme 2A).…”
mentioning
confidence: 99%